2017
DOI: 10.1186/s12937-017-0301-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between fruit and vegetable, and antioxidant nutrient intake and age-related macular degeneration by smoking status in elderly Korean men

Abstract: BackgroundAge-related macular degeneration (AMD) is one of the major causes of irreversible blindness. The objective of this study was to determine whether there is any relationship between dietary intake of fruits and vegetables (F&V) and antioxidant nutrients including carotenoids and AMD according to smoking status in elderly men.MethodsWe performed a cross-sectional analysis using nationally representative samples of elderly aged ≥ 65 years (n = 1414) from the Korea National Health and Nutrition Examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…In comparison, 83.5% of non-smokers had a healthy diet versus 16.5% of smokers. In this study, smoking had a negative effect on food, as other studies have also reported (62)(63) . A reduced variety of foods was also emphasized (62) .…”
Section: Discussionsupporting
confidence: 72%
“…In comparison, 83.5% of non-smokers had a healthy diet versus 16.5% of smokers. In this study, smoking had a negative effect on food, as other studies have also reported (62)(63) . A reduced variety of foods was also emphasized (62) .…”
Section: Discussionsupporting
confidence: 72%
“…In a study in South Korea, consumption of fruits and dairy products was lower among smokers than non-smokers, and smokers consumed fast foods more often than nonsmokers (61). Another Korean study also showed that smokers consumed vegetables less frequently than nonsmokers (62). Perhaps the positive association between vegetable consumption and smoking we observed might be an attempt to reduce the harmful effects of cigarette smoking.…”
Section: Discussionmentioning
confidence: 50%
“…The basal metabolism, physiological function and physical activity declined with age. As a result, the elderly were more likely to suffer health problems including poor handgrip strength, anemia, hip fracture, malnutrition, fatigue, cardiovascular disease, cognitive and frailty, back and neck pain and osteoarthritis, chronic obstructive pulmonary disease, diabetes, depression and geriatric syndromes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, elderly people tend to suffer from multiple diseases that may require more medical care and daily assistance in the world.…”
Section: Introductionmentioning
confidence: 99%